The Impact of Ribonucleotide Reductase Enzyme and Zinc on Leukemia - Mohammed, Maha Fadel; Shaker, Asmaa Hashim (American Journal of Biomedicine and Pharmacy, 2025)
Leukemia is a cancer that affects blood cells and their component tissues, such as the bone marrow and lymphatic system. It results from mutations in blood-forming stem cells, leading to abnormal cell growth and proliferation, which hinders normal blood formation. Types of blood cancer (acute myeloid leukemia (AML), acute lymphoblastic leukemia (ALL), chronic myeloid leukemia (CML), chronic lymphocytic leukemia (CLL) Symptoms: anemia, bleeding, recurrent infections, enlarged liver and spleen. Diagnosis: blood tests, bone marrow biopsy, genetic testing, and imaging. Treatment is of two types: chemotherapy (the primary treatment for AML, but its effectiveness decreases in older patients) or stem cell transplantation (used to improve outcomes, especially in younger patients). Ribonucleotide reductase: Scientific name: Ribonucleotide reductase EC 1.17.4.1 is an essential enzyme and a speed regulator in DNA synthesis, converting ribonucleotides (rNDPs) to deoxyribonucleotides (dNDPs), the building blocks of DNA. It is the enzyme The only known enzyme in cells that converts rNDP to dNDP, and is therefore essential for DNA replication and cell division. Its chemical structure is a complex enzyme consisting of two main protein subunits (RRM1 + RRM2), containing an iron-oxygen center essential for its enzymatic activity. It requires a tyrosine radical to carry out deoxygenation reactions. Its biological effect is the conversion of rNDP to dNDP, which is necessary for DNA synthesis and thus supports cell division, participates in DNA repair, and maintains the balance of nucleotide pools. Any enzyme defect leads to an imbalance in dNTPs → genetic mutations or DNA damage. Its relationship to leukemia: In leukemias (especially AML - Acute Myeloid Leukemia), cancer cells have an excessive need for dNTPs, so: enzyme activity increases significantly; RRM2 levels are particularly high in leukemia cells. The enzyme is considered An important target for cancer therapy. Zinc is an essential mineral with the chemical symbol Zn and atomic number 30. It is an important trace element in the human body and participates in many biochemical and enzymatic processes. It is found in all cells of the body and is concentrated in muscles, bones, skin, and liver. The body cannot store zinc in large quantities, so it must be obtained regularly from the diet. Patients with acute leukemia may suffer from zinc imbalance due to: Tumor lysis syndrome: zinc is released from dying cancer cells. Chemotherapy also affects the kidneys and electrolyte balance. Kidney dysfunction resulting from the disease. The study aims to understand the relationship between ribulose-5-phosphate isomerase activity and the effect of certain minerals, such as zinc, on the metabolic status of leukemia patients, to understand the biochemical mechanisms that contribute to the progression of the disease and its complications.